A symbiotic mosquito‐gut bacterium for flavivirus control - Jinglin Wang; Yibin Zhu; Jun Leng; Yulin Yuan; Yingyi Cao; Gong Cheng; Xueshan Xia (Clinical and Translational Medicine)
Abstract Dengue virus (DENV) and Zika virus (ZIKV) have emerged as major global public health challenges, causing numerous infections and fatalities each year. However, current measures, including vaccines and treatments, are often limited or ineffective. This highlights the urgent need for novel preventive strategies to control the spread of key mosquito‐borne viruses like DENV and ZIKV. In a recent study published in Science, Zhang et al. isolated a bacterium named Rosenbergiella_YN46 from the gut of field‐caught Aedes albopictus mosquitoes in Yunnan Province, China. This commentary reviews their findings, published on April 19, 2024, which describe the symbiotic bacterium Rosenbergiella_YN46 and its ability to block flavivirus transmission, including both DENV and ZIKV. The bacterium shows promising potential for future dengue fever prevention and provides valuable insights into a novel biological approach for controlling mosquito‐borne viral diseases.